Complete Systematic Land Registration - Saim Aksinuddin (Best Journal of Administration and Management, 2023)
Land registration is a series of activities carried out by the Government continuously, sustainably and regularly, including collecting, processing, bookkeeping, and presenting and maintaining physical data and juridical data. In land registration, it can happen that the object of land registration is encumbered by other rights such as: ownership rights, business use rights, building use rights, use rights, ownership rights over apartment units are used as collateral for debts and are encumbered with mortgage rights. The research method used is through a normative juridical approach, namely by inventorying, reviewing and analyzing and understanding the law as a set of positive norms in the legal system that regulates land registration issues in Indonesia. The results of this research explain that, based on the research results above, it can be concluded that, complete systematic land registration was carried out in the Majalengka Regency area. In 2019 Majalengka Regency distributed 26 thousand complete systematic land registration certificates spread across 2 sub-districts, namely Sindang Sub-district and Lemahsugih Sub-district. Then in 2020 Majalengka Regency again received a quota of 40 thousand complete systematic land registration certificates spread across several sub-districts. Problems of complete systematic land registration in Majalengka Regency, differentiated by time. Legal protection for complete systematic land registration in Majalengka Regency has been carried out well. In particular, regarding the rights of Majalengka residents to use the surface of the earth, along with the body of the earth, and the water and air space above it only as needed for purposes directly related to the use of the land in question.